ISOLASI FLAVONOID DARI EKSTRAK METANOL Drymaria cordata Willd SEBAGAI BAHANPEMBELAJARAN FITOKIMIA - Ruma K. S., Lusia Octora (Jurnal Pengembangan Pendidikan, 2006)
Abstract. Due to develop the potention of Drymaria cordataWilld. as a medicine from natural product, an experiment was done to isolatethe flavonoid from this plant. Flavonoid isolated by extraction with methanol,followed with fractionation using ethyl acetat and ethanol. Examination ofethanol fraction by thin layer chromatography with stationary phase silica gelGF 254 and mobile phase 15 % acetic acid showed phenolic compound ondetection with FeCl3 and gave yellow colour with amonia thatidentify flavonoid compound. Purification has done using column chromatographyand paper chromatography. The structureof two isolated compounds was identified by ultraviolet spectrophotometry. Thisexperiment can be used as laboratory practice or studied material onPhytochemistry Key words : Drymaria cordataWilld.,flavonoid, isolation